Comparison of short‐period daytime convective rainfall accumulations with total column precipitable water: Derivation of an operational forecasting technique. (23rd April 2020) - Young, Martin; Lamb, Daniel; Lane, Andrew; Lattimore, Chris
Abstract: A major forecasting challenge is predicting the likely intensity of rainfall in convective situations in which intense short‐period rainfall can lead to surface water flooding. The study demonstrates a useful correlation between precipitable water and 1 hr gauge‐derived rainfall accumulations in situations with deep instability and relatively slack flow in depth. The correlation forms the basis of a forecasting technique, independent of numerical weather prediction (NWP) model forecasts of rainfall, being applied at the UK's Met Office Flood Forecasting Centre (FFC). Abstract : Best‐fit lines from Figures 3 and 5 with the largest R 2 values plotted on one graph. Grey top 10%, blue top 1% and purple top 0.5% of gauges. The dashed green line shows "extreme totals" derived from the highest rates in each of the 5 mm precipitable water (PW) ranges shown in Figure 5. The forecasting technique derived from the graphs relates the PW (horizontal axis) to widespread (grey line), isolated (blue line), maximum (purple line) and extreme (dashed green line) hourly rainfall totals. For a more detailed interpretation of the lines, see the text.